2015
DOI: 10.1039/c5sc02586a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of diborane(4) with bridging B–H–B bonds

Abstract: The irradiation of diborane(6) dispersed in solid neon at 3 K with far-ultraviolet light generated diborane(4), B2H4, with bridging B–H–B bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 42 publications
(63 reference statements)
3
39
0
Order By: Relevance
“…According to Greenwood and Earnshaw, “Boron is a unique and exciting element… like C and Si, it shows a marked propensity to form covalent molecular compounds, but it differs sharply from them in having one less valence electron than the number of valence orbitals, a situation sometimes referred to as electron deficiency.” In view of its electron deficiency, boron has long been regarded as an electron‐acceptor atom. However, beginning in 1999, a few papers raised the possibility that boron may act as an electron‐pair donor . In 2011, we demonstrated that diborane (4) (B 2 H 4 ) could behave as an electron donor to form a hydrogen bond through its B−B covalent bond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Greenwood and Earnshaw, “Boron is a unique and exciting element… like C and Si, it shows a marked propensity to form covalent molecular compounds, but it differs sharply from them in having one less valence electron than the number of valence orbitals, a situation sometimes referred to as electron deficiency.” In view of its electron deficiency, boron has long been regarded as an electron‐acceptor atom. However, beginning in 1999, a few papers raised the possibility that boron may act as an electron‐pair donor . In 2011, we demonstrated that diborane (4) (B 2 H 4 ) could behave as an electron donor to form a hydrogen bond through its B−B covalent bond.…”
Section: Introductionmentioning
confidence: 99%
“…However,beginningi n1999, af ew papers raised the possibility that boron may act as an electron-pair donor. [2][3][4][5][6] In 2011, we demonstrated that diborane(4) (B 2 H 4 )c ould behave as an electron donor to form ah ydrogen bond through its BÀBc ovalent bond. Others have considered Ba sa ne lectron donor to form ah alogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, no neutral species has been identified experimentally until 2015, when Chou irradiated diborane (6) dispersed in neon at 3 K with far-ultraviolet light, detecting diborane(4), B 2 H 4 (Figure 1b). 40 This new species with two terminal hydrogen atoms possesses two bridging hydrogen atoms, and so it became the simplest neutral boron hydride identified with such a structural feature. (4).…”
Section: Diboranesmentioning
confidence: 99%
“…In the present article, we apply this theory to systems with electron-deficient bonds, i.e., to compounds which have too few valence electrons for the connections between atoms to be described as covalent bonds, and which have always fascinated chemists. First we apply the theory to the notoriously known textbook example of the diborane(6) 39 molecule (B 2 H 6 ) with two-electron threecenter bridge bonds and then also to recently characterized diborane(4) 40 (B 2 H 4 ) and zero-valent complexes of beryllium 41,42 . The neutral form of the latter compound exhibits surprising stability, which was attributed to a strong three-center two-electron π bond stretching across the C-Be-C core 41 .…”
Section: Introductionmentioning
confidence: 99%
“…The structure of B 2 H 6 involves bridging and contains two three‐centered bonds (as presented in Figure ). There are two stable isotopic variants of diborane: 80% and 20% for 11 B and 10 B, respectively . The most abundant species of diborane is 11 B 2 H 6 .…”
Section: Introductionmentioning
confidence: 99%